(untitled) (World Economics and Finance Bulletin, 2024)
The current research aims to identify On the nature of the relationship between soft skills and organization architecture,AndThe research problem was to look for leadership styles with capabilities and skills capable of bringing about the required changes, in line with the specificity of health organizations for their major role in improving the quality of services provided to a wide segment of the public in a way that contributes to the continuity of the organization.By providing services,And it was Questionnaire form a toolA major method for collecting data and information that was distributed to the sample, as it amounted to (50) An employee in the divisions and departments of Al-Rifai Teaching Hospital. The data was analyzed using a combination of descriptive and inferential statistical methods, including (standard deviation, arithmetic mean, relative importance,linear regression,Pearson correlation coefficient (through the statistical package)SPSS V 28, Excel). The research reached a set of conclusions, including